Physico-chemical Characteristics of Two Different Varieties of Sesame (Sesamum indicum L.) Seed Oil - Gul, Tahseen; Zreen, Zohra; Anwar*, Farooq; Sarwar, Shumaila (Asian Journal of Chemistry, 2011)
Sesame (Sesamum indicum L.) is an important oil seed crop. In the present research work, the physical and chemical characteristics of the oils extracted from indigenously available two varieties of sesame seeds are investigated. Proximate composition of sesame seeds (var. Pb-89 & TS-3) was as follow: oil content, 26.91, 30.48 %; moisture content, 17.30, 21.80 %; protein content, 31.00, 30.00 %; fiber content, 11.50, 10.00 % and ash content 5.50, 5.50 %, respectively. The extracted oils of the two varieties showed iodine value of 112,109; refractive index (40 °C), 1.4665, 1.4640; density (24 °C), 0.923,0.918; free fatty acid content, 0.45,0.51 %; saponification value, 183.0,178.8 mg of KOH /g of oil and unsaponifiable matter, 0.59,1.2 %, respectively. The oils analyzed exhibited good oxidative stability as evident from the determinations of peroxide value 2.20, 1.20; conjugated diene, 1.92, 0.91 and triene value, 0.95, 0.13, respectively. The level of a- and d-tocopherol in the oils of sesame (var. PB-89 & Ts-3) were 54.0, 62.0 and 0.0, 159.0 mg/kg, respectively. The fatty acid composition of sesame oil was as follows: palmitic acid (C16:0) 10.05 and 9.72 %, stearic acid (C18:0) 5.37 and 4.33 %, oleic acid (C18:1w-9) 41.29 and 36.22 %, linoleic acid (C18:2 w-6) 41.77 and 48.07 %, respectively. The present results showed the oil from both the sesame seed varieties varied significantly with regard to physico-chemical attributes.